Comparison of Physiological Adaptation and Osmoregulation Survival of Goldfish (Cyprinus carpio) and Nile Tilapia (Oreochromis niloticus) After Exposure to Seawater - Merta, I Wayan; Kusmiyati, Kusmiyati (Jurnal Biologi Tropis, 2025)
This study aims to: 1) compare the osmoregulatory physiological adaptation and survival of Goldfish (Cyprinus carpio) and Nile tilapia (Oreochromis niloticus) after exposure to seawater. 2) Increase the understanding of animal physiology course material, especially on the topic of osmoregulatory physiology of aquatic animals. Osmoregulation is an essential biological process that allows organisms, including fish, to maintain the balance of water and ions in their bodies. This process is closely related to homeostasis, which is the ability of the body to maintain internal stability despite changes in the external environment. This study uses an experimental design method. The research design involved two different treatment groups, one for goldfish (Cyprinus carpio) and one for Nile tilapia (Oreochromis niloticus), with each treatment replicated ten times. Each fish sample was exposed to seawater by placing it in a plastic bucket containing one liter of seawater. The release of the fish into the treatment medium was done simultaneously. Survival time was observed and recorded from the time the fish was exposed until it died. The breathing rate was observed by counting the opening and closing of the operculum for the first 5 minutes after the treatment for 1 minute, with the counting repeated every 5 minutes for 1 minute until the fish died, and then averaged. The data were analyzed using a t-test at a significance level of 5%. The t-test result showed t_observed = 24.232 > t_table = 2.101 at the 5% significance level with 18 degrees of freedom (df). The significance value (2-tailed Sig.) was 0.000, indicating that the difference between the two groups was highly significant (p < 0.05). This study concluded that Nile tilapia (Oreochromis niloticus) has a longer survival time compared to goldfish (Cyprinus carpio) when placed in seawater. The average survival time of Nile tilapia was 78.3 minutes, significantly longer than goldfish, which only survived for 16.8 minutes.